Effect of a null mutation of the insulin-like growth factor I receptor gene on growth and transformation of mouse embryo fibroblasts. - Sell, C (1994)
Fibroblast cell lines, designated R- and W cells, were generated, respectively, from mouse embryos homozygous for a targeted disruption of the Igf1r gene, encoding the type 1 insulin-like growth factor receptor, and from their wild-type littermates. W cells grow normally in serum-free medium supplemented with various combinations of purified growth factors, while pre- and postcrisis R- cells cannot grow, as they are arrested before entering the S phase. R- cells are able to grow in 10% serum, albeit more slowly than W cells, and with all phases of the cell cycle being elongated. An activated Ha-ras expressed from a stably transfected plasmid is unable to overcome the inability of R- cells to grow in serum-free medium supplemented with purified clones. Nevertheless, even in the presence of serum, R- cells stably transfected with Ha-ras, alone or in combination with simian virus 40 large T antigen, fail to form colonies in soft agar. Reintroduction into R- cells (or their derivatives) of a plasmid expressing the human insulin-like growth factor I receptor RNA and protein restores their ability to grow with purified growth factors or in soft agar. The signaling pathways participating in cell growth and transformation are discussed on the basis of these results.